MINAT DAN MOTIVASI PESERTA DIDIK KELAS X ELIND DALAM PEMBELAJARAN BAHASA INDONESIA DI SMK PUSDIKHUBAD CIMAHI - Narwati Narwati; Risma Novita Putri; Latifah Latifah (IKIP Siliwangi, 2019)
There are many assumptions that the interests and motivations of students can have a big influence on the process of learning Indonesian. Interest is a beginning of the process for students when trying to get knowledge that can be used for their intended interests and goals. While motivation is an insistence on yourself to carry out an activity to reach the goal. The purpose of this study is to see the desires and efforts of students while studying. Researchers use descriptive qualitative research methods and interview techniques. Evidence from this study states that the wishes and efforts of students while carrying out the learning process are still very lacking, because in Indonesian language material, the text is used so much especially with the added lack of students' desire to carry out minimal reading activities. That way, the learning process is not only focused on students but on skills when the teacher conveys learning, so that learning activities are not monotonous and are able to focus students' focus so that they are encouraged when their learning in Indonesian takes place. This can be concluded even though Indonesian is a lesson that must be learned in each school but it is possible that there are still students who are less interested and motivated in the main lesson, namely Indonesian.